TEACHERS’ STRATEGY OF POSITIONING IN TEACHING YOUNG LEARNERS - Restuningrum, Novi Rahayu (Prodi Administrasi Pendidikan Program Pascasarjana Universitas Riau, 2018)
Teacher’s position in the classroom depends on several aspects including the classroom s/he teaches in – whether s/he has the ability to move around – and the nature of the activities s/he is going to do in the class. As teacher's gestures including positioning and body posture bring the particular message to the students, the position whether a teacher should stand in front of the students, crouch down near them or sit with them on the floor needs to be considered when the teacher plans the lesson. This paper presents a discussion on how teachers of young learners position themselves in the classroom, the observed students’ behaviour during the lesson as the impacts of the positioning, and the teachers’ perspectives of the impacts of their positioning towards the students’ movement in the classroom. The study is done through observations towards an interview with two English teachers teaching classes of children of early years (4-5 years old), at a pre-school in Jakarta. It portrays a description of the teachers' position in the classroom and why they choose a particular position for a particular activity. The findings show that standing, sitting and kneeling in front of the students or among them is the most chosen position. Analysis on how students react to their lesson in relation to their position while teaching is also presented after a discussion on the reasons of teachers choosing their position in the classroom. As a final point, I elaborate the discussion on how teacher's positioning strategy can be implemented to help improving teacher's teaching practice. The presentation is envisioned for language teachers, language teaching researchers, teacher trainers, and those who are interested in the area of Teaching English to Young Learners (TEYL).